Influence of experimental fires on mesofauna communities (Collembola and Acari) of two types of meadows - Izabella Olejniczak; Stefan Russel; Anna Prędecka (Studia Ecologiae et Bioethicae)
The impact of prescribed fires in grasslands on soil mesofauna was studied in the field experiment. The study was carried out on two types of meadows: on mineral (meadow I) and organic soils (meadow II), near Warsaw (52o10’N; 20o50’E). In November 2007 sampling plots, 1 m2 in size were chosen at random and burned. Soil samples were taken just after fire and in April, July and November, 2008 to the depth of 10 cm from unburned plots (control), at the edge of fire and in burned plots. The soil mesofauna was extracted from soil samples in the Tullgren apparatus. There were not found any effects of prescribed fires on mesofauna densities. However, a slight increase of mesofauna abundance was observed on burned areas 12 months after experimental fires on the meadow I and decrease on the meadow II. Just after fire, on burned areas, only euedaphic species of Collembola were present among mites communities dominated Oribatida, with thick cuticule.